Literature Review: Effect of Peppermint on The Pain Level of Primary Dysmenorrhea - Maratus Sholichah Fitriah Hajar Kusnianto; Yeni Kartika Sari; Thatit Nurmawati; Handayani Handayani (Journal of Ners and Midwifery, 2023)
Dysmenorrhea is the most common menstrual disorder but is rarely understood by women. The pain experienced by women with dysmenorrhea causes discomfort and can affect mood. The aim of this study was to analyze the administration of peppermint therapy on the level and duration of primary dysmenorrhea pain. This study uses secondary data searched through the Science Direct, PubMed, and Pro-Quest databases, which discuss the effect of peppermint therapy to reduce dysmenorrhea pain. The study design of this research is Qualitative Systematic Literature Review. The research results showed 2 research articles that met the criteria stating that there was an effect of giving peppermint therapy on the level of dysmenorrhea pain.